Whole-rock geochemistry and crystal chemistry of apatite at intrusive suites of the Qeynarjeh-Angouran district (west of Zanjan): an approach to the identification of skarn-causative granitoids and magmatic-metallogenic evolutions - Afsoon Dastour; Ebrahim Tale Fazel; Ashraf Torkian (Journal of Economic Geology)
The Qeynarjah-Angouran district is located at the intersection of the Urumieh-Dokhtar and the Sanandaj-Sirjan structural zones in NW Iran. In this area, intrusive suites of Middle Triassic-Upper Jurassic age are exposed, including the Gharavol-Khane quartz diorite, the Kuh-e Belghais granite porphyry, and the Qeynarjeh granodiorites. Whole-rock geochemical data and crystal chemistry of apatite were analyzed to obtain the geochemical-metallogenic evolutions of magma and compare fertility using trace element interpolation. These intrusive suites with zircon saturation temperature (TZr) less than 900 °C and meta-aluminous to slightly peraluminous nature (A/CNK = 0.5-1.2) belong to the calc-alkaline series, which is evidence of I-type granitoids (Na2O/K2O = 0.8-2.0) in subduction zones (enrichment of LILE compared to HFSE along with P, Nb and Ti anomalies). ΣREE concentration, LREE/HREE ratio, and LILE content (including Rb, Ba, Th, U, K and Pb elements) in the Qeynarjeh granodiorites are determined to be twice as much as other intrusive suites, which are placed at a depth of 20 to 30 km of crust (Sr/Y=10-20), Rb/Sr ratio of whole-rock less than 0.4 and FeO content about 4 wt.% indicate characteristics of ore-bearing skarns. EPMA results show apatite crystals from Gharavol-Khane quartz diorite with high fluorine concentration (F = 2.2-2.7 wt.%) have been formed directly from the parent magma and Kuh-e Belghais granite porphyry apatites with high chlorine variation (Cl = 0.52-0.65 wt.%) is a result of large fluid-rock interactions between the granite porphyries and hydrothermal fluids. Overall, the Qeynarjeh granodiorites and the Gharavol-Khane quartz diorites show the most similarity with the petrogenesis-metallogenesis pattern of the iron skarn-causative intrusions.